2014
DOI: 10.1016/j.adolescence.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

National trends in school victimization among Asian American adolescents

Abstract: The model minority perception of Asian American students often ignores the academic and social challenges that many face in schools. One area that has received less attention is the school victimization experiences of Asian American adolescents. While some qualitative researchers have explored factors contributing to school victimization in recent years, missing in the literature is the scope of these incidents among Asian Americans. This paper contributes to this literature by (1) examining national trends in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…One study focused on a new subtopic, family communication on discrimination (Juang & Syed, 2014). Most studies targeted emerging adults ( n = 11; e.g., Kushins, 2014) or adults ( n = 8; e.g., Kushins, 2014), with only two studies focusing on adolescents (Cooc & Gee, 2014; Niwa, Way, & Hughes, 2014). Most studies used quantitative designs, such as experimental ( n = 4; e.g., Gibson, Losee, & Vitiello, 2014) and correlational designs, among which were cross-sectional ( n = 10; e.g., I.…”
Section: Resultsmentioning
confidence: 99%
“…One study focused on a new subtopic, family communication on discrimination (Juang & Syed, 2014). Most studies targeted emerging adults ( n = 11; e.g., Kushins, 2014) or adults ( n = 8; e.g., Kushins, 2014), with only two studies focusing on adolescents (Cooc & Gee, 2014; Niwa, Way, & Hughes, 2014). Most studies used quantitative designs, such as experimental ( n = 4; e.g., Gibson, Losee, & Vitiello, 2014) and correlational designs, among which were cross-sectional ( n = 10; e.g., I.…”
Section: Resultsmentioning
confidence: 99%
“…In a follow-up study focusing on Asian American and White students in the ELS dataset, Koo, Peguero, and Shekarkhar (2012) found that when they controlled for gender and immigrant status, Asian American youth were more likely to experience violent victimization at school than the White students. Findings regarding gender differences in experiences of victimization among Asian Americans remain conflicted with some finding that females experience more victimization (Koo et al, 2012), some reporting males have more experiences of victimization and harassment due to their perceived weakness and small stature (Qin, Way, & Rana, 2008); and others finding no gender differences (Cooc & Gee, 2014). Similarly, the research on victimization among high achieving Asian Americans is mixed with some reporting that high achieving Asian American students are more likely to be bullied (Peguero & Williams, 2013), and others finding they are less likely (Cooc & Gee, 2014).…”
Section: School Safetymentioning
confidence: 99%
“…Findings regarding gender differences in experiences of victimization among Asian Americans remain conflicted with some finding that females experience more victimization (Koo et al, 2012), some reporting males have more experiences of victimization and harassment due to their perceived weakness and small stature (Qin, Way, & Rana, 2008); and others finding no gender differences (Cooc & Gee, 2014). Similarly, the research on victimization among high achieving Asian Americans is mixed with some reporting that high achieving Asian American students are more likely to be bullied (Peguero & Williams, 2013), and others finding they are less likely (Cooc & Gee, 2014). The conflicting findings reflect the heterogeneity of Asian Americans and the need to understand the nuanced experiences of Asian American subgroups.…”
Section: School Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Physical beatings, verbal taunts mocking their home languages, racial slurs, and even bullying based on foods they bring from home-these are just some of the documented ways that Asian American adolescents nationwide experience the highest probability of racial discrimination in school (Cooc & Gee, 2014). In the wake of victimization, adolescents can face serious psychosocial consequences, including anxiety (Juvonen, Graham, & Schuster, 2003;Wolke & Lereya, 2015), depression (Juvonen et al, 2003;Klomek, Marrocco, Kleinman, Schonfeld, & Gould, 2007), and internalizing behavior problems (Wolke & Lereya, 2015), effects that can extend well into adulthood (Wolke & Lereya, 2015).…”
Section: Will I Be Victimized At School Today? How Schools Influence mentioning
confidence: 99%